Acceptance of Democracy and Sense of Adaptation to the Present Political System ? a Comparative Analysis of Beliefs among Students in Years 2003, 2008 and 2013 - Czerniawska, Mirosława (INSTED: Interdisciplinary Studies in Education & Society, 2017)
In the following article, one can find a diagnosis of convictions about democracy and the adaptation to the present political situation. The research was conducted among students of the Bialystok universities three times in years: 2003 (325 respondents), 2008 (379 respondents) and 2013 (368 respondents). An attempt was made to establish if (1) the approval of the democratic system, and (2) the sense of adaptation to the political system understood as the feeling of political capacity and identification with government policy (as opposed to the sense of political alienation) increased over time. The most positive attitude to the democracy and the adaptation to the political system (high political capacity and high identification with government policy) were observed in the year 2008. Contrary to the expectations ? a relatively higher percentage of students approved authoritarian government and were politically alienated in year 2013 in comparison to year 2008.